SISTEM KETATANEGARAAN REPUBLIK INDONESIA BERDASARKAN PANCASILA DAN UUD 1945 - Siti Awaliyah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: In conducting the state implementation, Indonesia as a state needs regulations in accordance with the national cultural values. The values are mirrored in Pancasilaas the spirit of constitutional laW which is The Constitution 1945. Indonesian governmental system is presidential; the president is the state chief and the governmental chief. The state power is in three powers, that are legislative, executive, andjudicial powers. Those three powers have relations in sharing the powers.This practice is not the same as the original theory of Montesquei about power divisions. In the implementation, The Constitution 1945 has supporting institutions. They are People's Consultative Council, House ofRepresentative, President, Supreme Court, Constitutional Council, Judicial Commission, Financial investigator, Police, and the Army.